Delayed Rectifier K(+)-Channel Is a Novel Therapeutic Target for Interstitial Renal Fibrosis in Rats with Unilateral Ureteral Obstruction - Abe, Nozomu (Biomed Res Int, 2019)
BACKGROUND: Delayed rectifier K(+)-channel, Kv1.3, is most predominantly expressed in T-lymphocytes and macrophages. In such leukocytes, Kv1.3-channels play pivotal roles in the activation and proliferation of cells, promoting cellular immunity. Since leukocyte-derived cytokines stimulate fibroblasts to produce collagen fibers in inflamed kidneys, Kv1.3-channels expressed in leukocytes would contribute to the progression of tubulointerstitial renal fibrosis. METHODS: Male Sprague-Dawley rats that underwent unilateral ureteral obstruction (UUO) were used at 1, 2, or 3 weeks after the operation. We examined the histological features of the kidneys and the leukocyte expression of Kv1.3-channels. We also examined the therapeutic effects of a selective channel inhibitor, margatoxin, on the progression of renal fibrosis and the proliferation of leukocytes within the cortical interstitium. RESULTS: In rat kidneys with UUO, progression of renal fibrosis and the infiltration of leukocytes became most prominent at 3 weeks after the operation, when Kv1.3-channels were overexpressed in proliferating leukocytes. In the cortical interstitium of margatoxin-treated UUO rat kidneys, immunohistochemistry revealed reduced expression of fibrosis markers. Additionally, margatoxin significantly decreased the numbers of leukocytes and suppressed their proliferation. CONCLUSIONS: This study clearly demonstrated that the numbers of T-lymphocytes and macrophages were markedly increased in UUO rat kidneys with longer postobstructive days. The overexpression of Kv1.3-channels in leukocytes was thought to be responsible for the proliferation of these cells and the progression of renal fibrosis. This study strongly suggested the therapeutic usefulness of targeting lymphocyte Kv1.3-channels in the treatment of renal fibrosis.